Structure Constants of Diagonal Reduction Algebras of gl Type - Khoroshkin, S.; Ogievetsky, O. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
We describe, in terms of generators and relations, the reduction algebra, related to the diagonal embedding of the Lie algebra gln into gln⊕gln. Its representation theory is related to the theory of decompositions of tensor products of gln-modules.